Kinesio tape reduces pain in patients with lateral epicondylitis: A meta-analysis of randomized controlled trials. (April 2020) - Zhong, Ying; Zheng, Cheng; Zheng, Jiahui; Xu, Shanchun
Abstract: Background: The efficacy of Kinesio tape (KT) in lateral epicondylitis (LE) is widely discussed, but the results of these studies are conflicting. We perform this meta-analysis from randomized controlled trials (RCTs) in order to evaluate the efficacy and safety of KT in the treatment of LE . Methods: A comprehensive search of the published literature in PUBMED, EMBASE, and Cochrane Library databases was implemented. Only English RCTs were included in this study. The outcome measures included visual analogue scale (VAS), grip strength, modified Mayo performance index, Disabilities of the Arm, Shoulder and Hand (DASH) score and adverse events. The Cochrane risk of bias tool was also utilized to evaluate the risk of bias. Data analysis was performed with STATA version 13.0 (Statacorp, college station, Tex). Results: Five studies with a total of 168 patients were included. The present meta-analysis demonstrated that KT yielded statistically superior pain scores, grip strength, Modified Mayo performance index and DASH score. There was no significant difference between the two groups in terms of adverse events. Conclusion: KT is effective in relieving pain, restoring grip strength, and improving functionality in patients with LE undergoing rehabilitation. Highlights: Kinesio tape (KT) is effective for reducing pain at rest and movement. KT is effective for recovering grip strength at 1 month and 3 month. The use of KT did not increase the risk of skin irritation.